Standards for the academic veterinary medical library - Murphy, Sarah Anne (Medical Library Association, 2005)
The Standards Committee of the Veterinary Medical Libraries Section was appointed in May 2000 and charged to create standards for the ideal academic veterinary medical library, written from the perspective of veterinary medical librarians. The resulting Standards for the Academic Veterinary Medical Library were approved by members of the Veterinary Medical Libraries Section during MLA '03 in San Diego, California. The standards were approved by Section Council in April 2005 and received final approval from the Board of Directors of the Medical Library Association during MLA '04 in Washington, DC.